2014
DOI: 10.1242/dev.104224
|View full text |Cite
|
Sign up to set email alerts
|

CXCR7 prevents excessive CXCL12-mediated downregulation of CXCR4 in migrating cortical interneurons

Abstract: The CXCL12/CXCR4 signaling pathway is involved in the development of numerous neuronal and non-neuronal structures. Recent work established that the atypical second CXCL12 receptor, CXCR7, is essential for the proper migration of interneuron precursors in the developing cerebral cortex. Two CXCR7-mediated functions were proposed in this process: direct modulation of β-arrestin-mediated signaling cascades and CXCL12 scavenging to regulate local chemokine availability and ensure responsiveness of the CXCL12/ CXC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
91
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(97 citation statements)
references
References 42 publications
6
91
0
Order By: Relevance
“…Several findings suggest that the chemokine CXCL12 (stromal cell-derived factor-1) via its receptors CXCR4 and CXCR7 acts as such a coordinating signal. First, in addition to the meninges, CXCL12 is highly expressed in IPCs and guides migrating interneurons in the cortex (Stumm et al, 2003;Tiveron et al, 2006;Stumm and Hollt, 2007;Li et al, 2008;Lysko et al, 2011;Wang et al, 2011;Abe et al, 2014). Second, we observed that CXCR4 is highly expressed in the forming thalamus and TCAs.…”
Section: Introductionmentioning
confidence: 53%
See 3 more Smart Citations
“…Several findings suggest that the chemokine CXCL12 (stromal cell-derived factor-1) via its receptors CXCR4 and CXCR7 acts as such a coordinating signal. First, in addition to the meninges, CXCL12 is highly expressed in IPCs and guides migrating interneurons in the cortex (Stumm et al, 2003;Tiveron et al, 2006;Stumm and Hollt, 2007;Li et al, 2008;Lysko et al, 2011;Wang et al, 2011;Abe et al, 2014). Second, we observed that CXCR4 is highly expressed in the forming thalamus and TCAs.…”
Section: Introductionmentioning
confidence: 53%
“…6F ). Quantification of interneuron distribution in the cortex has been described (Abe et al, 2014). Axon outgrowth from thalamus explants was quantified by measuring the 20 longest axons in each explant with ImageJ using the NeuronJ plug-in (illustrated in Fig.…”
Section: Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…It may act as a signaling receptor either independently or cooperatively with CXCR4. It is also possible that CXCR7 serves as a scavenger receptor to sequester CXCL12 to prevent excessive CXCL12-mediated CXCR4 downregulation via endocytosis, similar to what has been demonstrated for CXCR7 in the migration of the cortical interneurons (Abe et al, 2014).…”
Section: Primary Function Of Cxcl12/cxcr4 In Radial Glia Development mentioning
confidence: 67%